Pengaruh Lingkungan Kerja dan Beban Kerja terhadap Kinerja Pegawai Dinas Kependudukan dan Pencatatan Sipil Kota Jambi - Ristania Ria Rapella Sinaga; Sumarni Sumarni; Nur Hasanah (Politeknik Kampar, 2024)
This research aims to determine the influence of the work environment and workload on employee performance of Jambi City Population and Civil Registration Service employees. This research uses quantitative methods with data collection techniques by distributing questionnaires to 88 respondents. Hypothesis testing was carried out using descriptive analysis techniques the IBM SPSS 29 software application. The result of this research show that the Work Environment partially has a significant and positive effect on employee performance, workload partially has a significant and positive effect on employee performance, then work environment and workload simultaneously has significant and positive effect on the performance of Jambi City Population and Civil Regristration Service employees.